AKR1B10 induces cell resistance to daunorubicin and idarubicin by reducing C13 ketonic group - Zhong, Linlin; Shen, Honglin; Huang, Chenfei; Jing, Hongwu; Cao, Deliang (Toxicology and applied pharmacology, 2011)
Daunorubicin, idarubicin, doxorubicin and epirubicin are anthracyclines widely used for the treatment of lymphoma, leukemia, and breast, lung, and liver cancers, but tumor resistance limits their clinical success. Aldo-keto reductase family 1 B10 (AKR1B10) is an NADPH-dependent enzyme overexpressed in liver and lung carcinomas. This study was aimed to determine the role of AKR1B10 in tumor resistance to anthracyclines. AKR1B10 activity toward anthracyclines was measured using recombinant protein. Cell resistance to anthracycline was determined by ectopic expression of AKR1B10 or inhibition by epalrestat. Results showed that AKR1B10 reduces C13-ketonic group on side chain of daunorubicin and idarubicin to hydroxyl forms. In vitro, AKR1B10 converted daunorubicin to daunorubicinol at V max of 837.42 ± 81.39 nmol/mg/min, K m of 9.317 ± 2.25 mM and k cat / K m of 3.24. AKR1B10 showed better catalytic efficiency toward idarubicin with V max at 460.23 ± 28.12 nmol/mg/min, K m at 0.461 ± 0.09 mM and k cat / K m at 35.94. AKR1B10 was less active toward doxorubicin and epirubicin with a C14-hydroxyl group. In living cells, AKR1B10 efficiently catalyzed reduction of daunorubicin (50 nM) and idarubicin (30 nM) to corresponding alcohols. Within 24 h, approximately 20 ± 2.7% of daunorubicin (1 μM) or 23 ± 2.3% of idarubicin (1 μM) was converted to daunorubicinol or idarubicinol in AKR1B10 expression cells compared to 7 ± 0.9% and 5 ± 1.5% in vector control. AKR1B10 expression led to cell resistance to daunorubicin and idarubicin, but inhibitor epalrestat showed a synergistic role with these agents. Together our data suggest that AKR1B10 participates in cellular metabolism of daunorubicin and idarubicin, resulting in drug resistance. These data are informative for the clinical use of idarubicin and daunorubicin. ► This study defines enzyme activity of AKR1B10 protein towards daunorubicin, idarubicin, doxorubicin, and epirubicin. ► This study pinpoints the chemical group—C13 ketone that AKR1B10 acts on. ► This study identifies that the C14 group (methyl or hydroxyl) affects the substrate specificity towards AKR1B10. ► This study defines the role of AKR1B10 in cellular metabolism and pharmacokinetics of anthracyclines. ► This study demonstrates the role of AKR1B10 in cell resistance to anthracyclines in an in vitro cell culture model.